Screening of sesame (Sesamum indicum L.) genotypes for resistance toleafhopper and phyllody disease under field conditions: SCREENING OF SESAME GENOTYPES FOR RESISTANCE TO LEAFHOPPER AND PHYLLODY DISEASE - S PREETH; K SUNIL KUMAR; K MANJULA; P SRIVALLI (Journal of Oilseeds Research, 2026)
A field screening experiment was conducted to evaluate the reaction of 30 sesame genotypes, along with a susceptible check (YLM-66), against the sesame leafhopper and phyllody disease under natural field conditions. Leafhopper nymphal populations were recorded at 21, 28, 36, 44, 52, and 60 days after sowing (DAS), while the percentage incidence of phyllody disease was assessed at the corresponding crop stages. The data were analyzed using analysis of variance (ANOVA) under a Randomized Block Design at the 5% level of significance. The mean leafhopper population ranged from 0.0 to 6.0 nymphs per three leaves, whereas phyllody disease incidence varied from 0.0% to 75.4% among the genotypes. Based on cumulative phyllody incidence and a seven-point disease reaction scale, the genotypes were classified into resistant, moderately resistant, tolerant, moderately susceptible, susceptible, and highly susceptible categories. Three genotypes, namely UTS-39 (4.4%), DS-10 (5.7%), and GT-10 (9.7%), recorded the lowest leafhopper populations and phyllody disease incidence and were identified as resistant under the conditions of this study. In contrast, IC-205354 (75.4%), YLM-W-154 (73.5%), and YLM-66 (74.5%) exhibited high leafhopper infestation and severe phyllody incidence and were categorized as highly susceptible. A positive correlation was observed between leafhopper population and phyllody disease incidence in sesame. The remaining genotypes exhibited varying levels of resistance and susceptibility.